Cytochrome C as a potential clinical marker for diagnosis and treatment of glioma - Rana, Rashmi; Huirem, Rohit Singh; Kant, Ravi; Chauhan, Kirti; Sharma, Swati; Yashavarddhan, M. H.; Chhabra, Satnam Singh; Acharya, Rajesh; Kalra, Samir Kumar; Gupta, Anshul; Jain, Sunila; Ganguly, Nirmal Kumar (Frontiers in Oncology, 2022)
Gliomas are the most prevalent kind of malignant and severe brain cancer. Apoptosis regulating mechanisms are disturbed in malignant gliomas, as they are in added forms of malignancy. Understanding apoptosis and other associated processes are thought to be critical for understanding the origins of malignant tumors and designing anti-cancerous drugs for the treatment. The purpose of this study was to evaluate the variation in the expression level of several apoptotic proteins that are responsible for apoptosis in low to high-grade glioma. This suggests a significant change in the expression of five apoptotic proteins: Clusterin, HSP27, Catalase, Cytochrome C, and SMAC. Cytochrome C, one of the five substantially altered proteins, is a crucial component of the apoptotic cascade. The complex enzyme Cytochrome C is involved in metabolic pathways such as respiration and cell death. The results demonstrated that Cytochrome C expression levels are lower in glioma tissues than in normal tissues. What's more intriguing is that the expression level decreases with an increase in glioma grades. As a result, the discovery shows that Cytochrome C may be a target for glioma prognostic biomarkers.